Pengaruh Pendidikan Entrepreneurship Terhadap Minat Berwirausaha Pada Mahasiswa Fakultas Ekonomi Universitas Sumatera Barat - Marshal Imar Pratama (CV. ITTC INDONESIA, 2024)
This research is entitled The Influence of Entrepreneurship Education on Interest in Entrepreneurship in Economics Faculty Students at the University of West Sumatra. This research is motivated by the need for Economics faculty students to be able to create their own jobs with the skills or education they have received. No need to wait for the relevant agency to open job vacancies. This research uses a quantitative type of research. The data taken was primary data by distributing questionnaires to students at the Faculty of Economics at the University of West Sumatra. This research carried out research instrument tests, classical assumption tests, hypothesis tests using SPSS version 21. The research results stated that looking at the test results that had been carried out proved that partially the variables had a significant effect, and it could also be seen that the Adjusted R Square was 0.370 or 37%. This means that the entrepreneurial interest variable is influenced by entrepreneurship education and the remaining 63% is influenced by other variables outside of this research variable.